Application of High-quality Bathymetry to Geological Interpretation on the Scotian Shelf - Loncarevic, Bosco; Piper, David; Fader, Gordon (Geoscience Canada, 1992)
Abstracts Techniques are now available to prepare bathymétrie maps of the sea floor with detail similar to that of topographic maps on land. Gridded data sets can be displayed as shad-owgrams to enhance particular morphologic features. Glacial geomorphological features on the continental shelf off eastern Canadacan be interpreted in a manner analogous toglacial features on land. The last major dataset acquired by the CSS BAFFIN from the eastern Scotian Shelf shows a complex topography interpreted as a series of glacial tunnel valleys, which indicate several episodes of sub-glacial meltwater flow anderosion.